Argumentation, the study of effective reasoning - Zarefsky, David (Great courses (Audiocassette), 2001)
Dr. David Zarefsky, professor of communication studies at Northwestern University, delivers lectures covering the history of rhetoric and debate as well as analysis of different types of arguments in various situations.